Acute post streptococcal glomerulonephritis at Red Cross War Memorial Children's Hospital, Cape Town, South Africa - a five-and half-year descriptive review - Abugrain, Khadija (Department of Paediatrics and Child Health, 2023)
Background: Acute post streptococcal glomerulonephritis (APSGN), although not a common cause of progressive kidney failure, is an important cause of paediatric hospital admission, parental worry, and acute kidney injury (AKI). In well-resourced settings, there has been a decline over the last three decades in the incidence of APSGN in children with this condition almost disappearing in Central Europe. However, this is not the case in less privileged countries such as in South Africa (SA) where APSGN is still a major public health problem and a frequent cause of paediatric hospital admission and AKI. Nevertheless, APSGN in South Africa has not been studied adequately in recent times and not currently addressed as an important public health issue. Objectives: In this retrospective study we describe the occurrence of APSGN, the aetiology, clinical presentation, and complications among children (<14years) admitted to the Red Cross War Memorial Children's Hospital (RCWMCH) in Cape Town, SA from January 2015 to June 2020. Methods: The hospital electronic database with recorded ICD-10 coding was used to identify potential cases of acute nephritic syndrome. Children were included if they presented with at least two signs of acute nephritis, associated with evidence of activation of an alternative pathway complement system (low C3 serum level) or clinical and serological evidence of previous or current streptococcal infection. Demographic, clinical features, investigations, management, and outcome data were collected. Data were presented as median and interquartile ranges (IQR) or means and standard deviation (SD) depending on normality of data while proportions of categorical data were presented as percentages. Population incidences were calculated from the four major health districts within the drainage areas for RCWMCH. This study was conducted in accordance with the 2013 Declaration of Helsinki and was approved by RCWMCH administration and the University of Cape Town's Human Research Ethics Committee, (HREC: 623/2020). Results: There were 157 children with suspected acute nephritic syndrome (haematuria, oedema, oliguria and hypertension), of whom 96 met the inclusion criteria and were recruited. Of the 96 children included in the study, 89 (93%) cases had confirmed APSGN, and seven (7%) children had a clinical diagnosis of rapidly progressive glomerulonephritis (RPGN), with positive streptococcal serology and crescentic glomerulonephritis in the kidney biopsy. APSGN occurred in 61 (63%) children aged five to ten years with 62 (65%) males (ratio of 1.9:1). APSGN was more often associated with streptococcal skin infections (55%). The majority 95 (99%) of cases presented with haematuria, while proteinuria was noted in 85 children. Seventy-one (74%) children presented in stage 2 hypertension, with 10 (10%) presenting with hypertensive seizures. Serum C3 levels were low in 83 (87%) children. 90 (94%) children had elevated anti-deoxyribonuclease B antibodies (anti-DNase-B) levels, and 77 (80%) also had elevated anti-streptolysin O titres (ASOT) titres at presentation. Eighty-eight (92%) children received a diuretic agent, 60 (63%) required an anti-hypertensive agent, and 90 (94%) received a penicillin antibiotic for 10 days. The median length of hospital stay was five (IQR 3-6) days. There were no deaths. Eighty-one (85%) children with APSGN recovered. Five (5%) progressed to end stage kidney disease (ESKD). A percutaneous kidney biopsy was indicated in eleven (11%) children. Seven (64%) biopsies confirmed type II crescentic glomerulonephritis, and four (36%) biopsies showed histological features of post-infectious nephritis. Conclusion: APSGN during childhood remains an important health problem in SA and commonly follows streptococcal skin infection. The outcome is favourable in most children; however, our study revealed an important sub-group with crescentic glomerulonephritis who progressed to ESKD. We recommend active case seeking at primary care level by checking urine dipstick, blood pressure and serum creatinine and better post-discharge follow up.